PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 75 PETANI KECAMATAN MANDAU KABUPATEN BENGKALIS - ', Emitati; Marhadi, Hendri; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
bstrak : This research was conducted because of the result of learning IPA class III SD Negeri 75 Petani. From 25 student who achieve KKM just 12 student (48 while student who did’nt complete 13 student (52%) with an average of 57,29. This aims of study to increased study result IPA school years 2015-2016. This research subjet are student class III SDN 75 Petani Kecamatan Mandau kabupaten Bengkalis with amount of 25 students. This research is the action research class with the cycle two. This case can prove with the actiuty teacher score on each appintment have increased. The first appointment teacher activity presentation is 60% with the enough category and the second appointment to 70.8% with good category. On the one cycle two appointment increased 79,2% with the good category and the two cycle two appointment increased again to 87,5% with the excellent category. SStudent activity on the first appointment to 62,5% with the enough category and the second appointment to 66,7% with the enough category.The one cycle two appincreased again to 83,3 with the excellent category. Studies result on the first score only 12 student 48%have completed and increased on the first exam 1 to 15 student 60% and increased again on the second day exam 2 to 22 student person applied on the learning model cooperative type Numbered head together can increased studies IPA student class III SDN 75 Petani Kecamatan Mandau Kabupaten Bengkalis. Key Words : Numbered Head Together, Learning Outcomes IPA